Ventricular assist device for a coronavirus disease 2019‐affected heart. (20th November 2020) - Rassaf, Tienush; Totzeck, Matthias; Mahabadi, Amir A.; Hendgen‐Cotta, Ulrike; Korste, Sebastian; Settelmeier, Stephan; Luedike, Peter; Dittmer, Ulf; Herbstreit, Frank; Brenner, Thorsten; Klingel, Karin; Hasenberg, Mike; et al.
Abstract: Coronavirus disease 2019 (COVID‐19) is challenging the care for cardiovascular patients, resulting in serious consequences with increasing mortality in pre‐diseased heart failure patients. In the current state of the pandemic, the physiopathology of COVID‐19 affecting pre‐diseased hearts and the management of terminal heart failure in COVID‐19 patients remain unclear. We outline the findings of a young COVID‐19 patient suffering from idiopathic cardiomyopathy who was treated for acute multi‐organ failure and required cardiac surgery with implantation of a temporary right ventricular and durable left ventricular assist device (LVAD). For deeper translational insights, we used in‐depth tissue analysis by electron and light sheet fluorescence microscopy revealing evidence for spatial distribution of severe acute respiratory syndrome coronavirus 2 in the heart. This indicates that in‐depth analysis may represent a valuable tool in understanding indistinct clinical cases. We conclude that COVID‐19 directly affects pre‐diseased hearts, but the consequences can be treated successfully with LVAD implantation.